2018
DOI: 10.1002/cam4.1286
|View full text |Cite
|
Sign up to set email alerts
|

Can therapeutic drug monitoring increase the safety of Imatinib in GIST patients?

Abstract: Imatinib at 400 mg daily is the standard treatment for patients affected with CML and GIST. The intervariability in plasma concentration is very significant. In many reports, a good therapeutic effect is attributed to an adequate concentration of Imatinib. However, few studies have been conducted to investigate the association between plasma concentration and side effects. Besides, no upper concentration limit of Imatinib plasma concentration detection has been established. The correlation of Imatinib trough c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“… 31 We believe that the differences in AEs between the 2 drugs would not be affected, even if the 2 types of diseases treated with imatinib were included in the analysis. Third, some AEs, such as pleural effusion and myelosuppression, 32 , 33 are known to be dependent on the dose of TKIs. In the present study, the mean doses of dasatinib and imatinib were 98.8±26.8 and 356.8±87.3 mg daily, respectively, which correspond to the standard doses for these drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 31 We believe that the differences in AEs between the 2 drugs would not be affected, even if the 2 types of diseases treated with imatinib were included in the analysis. Third, some AEs, such as pleural effusion and myelosuppression, 32 , 33 are known to be dependent on the dose of TKIs. In the present study, the mean doses of dasatinib and imatinib were 98.8±26.8 and 356.8±87.3 mg daily, respectively, which correspond to the standard doses for these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…50 Another study shows that patients with higher blood concentrations are more likely to develop thrombocytopenia, 51 and that patients with blood concentrations of higher than 1451.6 ng/mL of IM were more likely to develop myelosuppression. 52 A study found that higher protein levels in the body can significantly reduce the concentrations of free IM and N-desmethyl-imatinib, thus affecting their pharmacological effects. This study also found that the adverse effects of IM were related to the blood concentration of N-desmethyl-imatinib.…”
Section: Toxic or Adverse Effects Caused By High Blood Concentration mentioning
confidence: 99%
“…In this section, we focus on the factors affecting the plasma concentrations of IM in patients with GISTs or CML, respectively. Because the potency of NDI is similar to that of IM in vitro, the concentration of NDI is frequently determined along with IM concentrations in TDM studies (Zhuang et al, 2018).…”
Section: Factors Affecting the Plasma Concentrations Of Imatinib Mesymentioning
confidence: 99%
“…Interpatient differences in therapeutic response may occur partly because of pharmacokinetic (PK) variability, which has been estimated to be ∼60 and 71% in IM steady-state trough concentrations in patients with GISTs or CML, respectively (Gandia et al, 2013;Zhuang et al, 2018). PK variability, which is mainly caused by physiological, pathological, genetic, demographic, and environmental factors, manifests as a broad range of plasma trough levels (C min ) in patients receiving the same dosage, usually 400 mg/d of IM (Widmer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%